Effects of forest conversion on the aquatic Coleoptera assemblage in Mediterranean-climate streams. (April 2020) - Fierro, Pablo; Ferrú, Marcos; Lara, Carlos
Highlights: Land use types can be assessed using Coleoptera assemblage. 18 streams distributed in native forest, agriculture and urban areas were assessed. 5 taxa were recorded in native forest, 5 in agriculture and 3 in urban streams. Hydraenidae individuals appear to be the most tolerant taxon. Coleopteran taxa were responsive to cobble proportion. Abstract: The aquatic Coleoptera in a Mediterranean climate region were studied in order to assess the main factors affecting the assemblage structure. We tested the effects of different land use types (native forest, agriculture and urban) on environmental features and water beetles in Chilean streams. Eighteen stream sites were sampled in the austral summer of 2016. Physical variables including water temperature, dry width of channel, altitude, proportion of fine sediment, gravel/pebbles and boulders were significantly different among land uses. Eight Coleoptera taxa were collected across all sites; five were recorded in native forest and agriculture streams and three in urban streams. The riffle beetles Stethelmis chilensis, Austrelmis sp., Austrolimnius sp. and Tychepsephenus felix were found in native forest and in low density in agriculture streams. Hydraenidae appear to be the most tolerant taxon, dominant in agriculture and urban streams. Canonical analysis of principal coordinates based on environmental features and Coleoptera density data showed a clear separation of native forest streams from agriculture and urban area streams. Using distance-based linear models, cobble proportion was the most important variable structuring the water beetle assemblage. Our findings suggest that aquatic beetles are good ecological indicators of anthropogenic land use types in aquatic ecosystems in Mediterranean streams. This is the first study using aquatic coleopteran species for Chilean Mediterranean streams. Our study highlights the importance of the native forest for the conservation of stream insects.